Optimal sizing of wind-hydrogen system considering hydrogen demand and trading modes. (14th April 2020) - Deng, Zhihong; Jiang, Yuewen
Abstract: In order to make full use of renewable energy and improve the utilization of wind power, a new joint optimization scheme of the wind-hydrogen system coupled with transmission project is proposed in this paper, in which wind power is reasonably allocated for grid integration and for hydrogen production. Aiming at maximize the annul wind-hydrogen system benefit, the optimal sizes of wind power transmission project and hydrogen system are obtained under different hydrogen production modes, hydrogen trading modes and hydrogen demand levels. In addition, the penalty cost of wind curtailment and hydrogen supply shortage and the system environmental benefits are taken into account. Results show: during the long-term of insufficient of wind power, it is better to produce hydrogen using wind power and grid-assisted power to avoid hydrogen supply shortage; considering the future increase of hydrogen demand, the optimal supply number of hydrogen refueling stations in the wind-hydrogen system is two. Also, the low utilization of fuel cells means that the benefit from regeneration cannot offset the high cost, which leads to the abnegation of fuel cells in the wind-hydrogen system. Graphical abstract: Image 1 Highlights: Sizing of a wind-hydrogen system considering transmission project is proposed. Contract trading and free market trading for hydrogen sale are explored. Sizing with different hydrogen demand, production and trading modes is studied. Producing hydrogen by wind and grid-assisted power is more beneficial.